Oral antimicrobial peptides: Types and role in the oral cavity - Zohaib Khurshid; Mustafa Naseem; Zeeshan Sheikh; Shariq Najeeb; Sana Shahab; Muhammad Sohail Zafar (Elsevier, 2016)
Antimicrobial peptides (AMPs) are a wide-ranging class of host-defense molecules that act early to contest against microbial invasion and challenge. These are small cationic peptides that play an important in the development of innate immunity. In the oral cavity, the AMPs are produced by the salivary glands and the oral epithelium and serve defensive purposes. The aim of this review was to discuss the types and functions of oral AMPs and their role in combating microorganisms and infections in the oral cavity.